1966
DOI: 10.1128/jb.91.2.870-875.1966
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Bacterial Flagella I. Demonstration of a Functional Flagellin Pool in Spirillum serpens and Bacillus subtilis

Abstract: Angeles), AND E. Z. GORDEE. Formation of bacterial flagella. I. Demonstration of a functional flagellin pool in Spirillum serpens and Bacillus subtilis. J. Bacteriol. 91:870-875. 1966-Exponentially growing cultures of Spirillum serpens and Bacillus subtilis regained motility and flagella within one generation after mechanical deflagellation. Regeneration of flagella occurred in both cultures in the presence of chloramphenicol at concentrations shown to inhibit flagellin synthesis. Cells labeled with C'4-amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 14 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…When S. serpens divides, each daughter cell inherits a tuft of flagella at one end and grows a tuft at the other. The inherited tuft stays the same size as at division (151). However, Martinez and Gordee observed that if the cell is deflagellated, both ends grow fresh tufts.…”
Section: Ciation a Similar Argument Holds For G-actin Polymerizationmentioning
confidence: 88%
“…When S. serpens divides, each daughter cell inherits a tuft of flagella at one end and grows a tuft at the other. The inherited tuft stays the same size as at division (151). However, Martinez and Gordee observed that if the cell is deflagellated, both ends grow fresh tufts.…”
Section: Ciation a Similar Argument Holds For G-actin Polymerizationmentioning
confidence: 88%
“…An attractive feature of structural models such as this one is the stimulus to correlate morphogenetic information. There is evidence that monomeric flagellin protein is synthesized on ribosomes (14), and subsequently it must somehow be directed towards the cell envelope for "export." Since flagella are also known to extend in length by addition of subunits at their distal end (12), a mechanism for the transport of flagellin must be invoked.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a functional flagellin pool in bacterial cells was inferred from Ouchterlony or quantitative precipitation tests on cell lysates of P. vulgaris and B. subtilis (D. Nasser and H. Koffler, Bacteriol Proc., p. 35, 1963; D. Weinstein, H. Koffler, and M. Moskowitz, Bacteriol. Proc., p. 63,1960) and also from the regeneration experiment on flagella of B. subtilis (148). However, Kerridge (109) studied the kinetics of isotope incorporation into flagella, and concluded that a functional pool of flagellin is not present in S. typhimurium.…”
Section: Initiation Of Polymerization Of Flagellinmentioning
confidence: 99%